Meta-analysis of Genetic Variation in DTNBP1 and General Cognitive Ability - Zhang, Jian-Ping (2010)
BACKGROUND: The human dystrobrevin-binding protein 1 (DTNBP1) gene has been linked to risk for schizophrenia. Recent studies indicate that several single nucleotide polymorphisms (SNPs) in the DTNBP1 gene may also influence general cognitive ability in both schizophrenic patients and healthy controls. We examined the relationship between DTNBP1 SNPs and general cognitive ability in non-psychiatric healthy samples via meta-analysis. METHODS: Medline search (12/31/2009) yielded 11 articles examining DTNBP1 variation and general cognitive ability, of which 8 studies had data available encompassing 10 independent cohorts (total n=7,592). The phenotype was defined as either the first principal component score from multiple neuropsychological tests (Spearman's g) or full scale IQ. Meta-analyses were conducted for 9 SNPs for which cognitive data were available from at least 3 cohorts. For each SNP in each cohort, effect size (ES) was computed between major allele homozygotes and minor allele carriers; ES was then pooled across studies using a random effect model. RESULTS: Pooled ES's from 2 of the 9 SNPs (rs1018381 and rs2619522) were -0.123 and -0.083, p's<0.01, respectively, suggesting that the minor allele carriers of these SNPs had lower cognitive ability scores than the major allele homozygotes. Results remained significant after examining heterogeneity among samples and potential publication biases. Other SNPs did not show significant effects on general cognitive ability. CONCLUSION: Genetic variation in DTNBP1 modestly influences general cognitive ability. Further studies are needed to elucidate the biological mechanisms that may account for this relationship.